Urgensi Studi Pancasila Sebagai Kristalisasi Peradaban Bangsa Indonesia - Adon, Mathias Jebaru; Mangisengi, Antonius; Marianto, Firminus; Barak, Antonius (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the historical-cultural basis of Pancasila and to analyze the urgency of studying Pancasila as the identity of the Indonesian nation. This study used the literature study method with phenomenological analysis. The historical-cultural foundation of Pancasila, namely Pancasila, originated from the thoughts and habits of the Indonesian people, which had lasted since the ethnic era, the kingdom era, the colonial era, and the era of the national movement until now. Ethnic groups had a pattern of life that was very compact, friendly, and harmonious and lived with a family spirit. The Majapahit Kingdom and the Sriwijaya Kingdom were the pioneers in the formation of the unity of Indonesia. The Dutch East Indies colonial era raised national and state awareness because of shared destiny and struggle. The founder of the state ultimately formulated the values of the character of the Indonesian nation known as Pancasila as the identity of the Indonesian nation. The urgency of studying Pancasila as the identity of the Indonesian nation was the increasing prevalence of acts of terrorism and radicalism that threaten the integrity of the unitary state of the Republic of Indonesia. Acts of terrorism and radicalism could be minimized if the Indonesian people realized that Pancasila is essentially a wisdom that has been possessed for thousands of years.